Integrasi Video Conference dalam Aplikasi Pembelajaran Siswa Sekolah Dasar untuk Kemudahan Interaksi dan Evaluasi Proses Belajar Mengajar Secara Daring - Agus Hermanto; Mochamad Sidqon (Universitas Asahan, 2020)
Abstract - The rapid development of information technology is one of the most valuable potentials in efforts to improve the quality of education. With information technology, there is a lot of unlimited information that can be extracted for the benefit of the development of the world of education. SDN Karangsentul, which is the object of community service in this study, also does not escape and must be able to adapt to technological developments during teaching and learning activities. One form of implementing the use of technology in the world of education is an online teaching and learning system. In online learning, it is necessary to pay attention to the ease of interaction and evaluation in these learning activities. One of the efforts to improve the ease of interaction and evaluation of learning is by integrating online learning with the video conference feature. Based on these considerations to facilitate the interaction and evaluation of the online learning process, this community service activity will carry out the Integration of Video Conferences in Primary School Student Learning Applications for Ease of Interaction and Evaluation of the Online Teaching and Learning Process, so that online learning support can have a maximum impact on education development. In its construction, the SDLC method is used. And used white-box testing methods and BlackBox testing. The test results show that the system built works well and is able to answer existing problems.Keywords - Online, Education, Community Service, Information Technology, Video Conference. Abstrak - Teknologi informasi yang berkembang semakin pesat merupakan salah satu potensi berharga dalam upaya peningkatan kualitas pendidikan. Dengan teknologi informasi banyak sekali informasi yang tak terbatas yang dapat digali demi kepentingan perkembangan dunia Pendidikan. Salah satu bentuk implementasi pemanfaatan teknologi dalam dunia Pendidikan adalah sistem belajar mengajar daring. Dalam pembelajaran daring, perlu diperhatikan kemudahan interaksi dan evaluasi dalam kegiatan pembelajaran tersebut. Salah satu upaya untuk meningkatkan kemudahan interaksi dan evaluasi pembelajaran adalah dengan mengintegrasikan pembelajaran daring dengan fitur video conference. Berdasarkan pertimbangan tersebut dalam rangka mempermudah interaksi dan evaluasi proses pembelajaran daring, pada kegiatan pengabdian masyarakat ini akan dilaksanakan Integrasi Video Conferece Dalam Aplikasi Pembelajaran Siswa Sekolah Dasar Untuk Kemudahan Interaksi dan Evaluasi Proses Belajar Mengajar Secara Daring, sehingga dukungan pembelajaran daring dapat berdampak maksimal pada perkembangan Pendidikan. Pada pembangunannya digunakan metode SDLC. Serta digunakan metode pengujian whitebox dan blackbox testing. Hasil pengujian menunjukkan sistem yang dibangun berhasil dengan baik dan mampu menjawab permasalahan yang ada. Kata Kunci - Daring, Pendidikan, Pengabdian Masyarakat, Teknologi Informasi, Video Conference.